2016
DOI: 10.1158/1078-0432.ccr-14-3379
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin Depletes Specificity Protein 1 and Activates p53 to Mediate Senescence and Apoptosis of Malignant Pleural Mesothelioma Cells

Abstract: Purpose Specificity protein 1 (SP1) is an oncogenic transcription factor over-expressed in various human malignancies. This study sought to examine SP1 expression in malignant pleural mesotheliomas (MPM), and ascertain the potential efficacy of targeting SP1 in these neoplasms. Experimental Design qRT-PCR, immunoblot and immunohistochemistry techniques were used to evaluate SP1 expression in cultured MPM cells and MPM specimens and normal mesothelial cells/pleura. MTS, chemotaxis, soft agar, ß-galactosidase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Functional consequences of deregulations in ZEB1, ERβ, SP1, and WT1 zinc-finger transcription factors are well studied in breast cancer, lung cancer, pancreatic cancer, and prostate cancer [ 169 , 170 , 171 , 172 ]. Recently, the upregulation of these genes has been shown in MPM, when compared to matched normal counterparts [ 173 , 174 , 175 , 176 ]. Horio et al showed that siRNA-mediated knockdown of ZEB1 (zinc finger e-box binding homeobox 1) led to the suppression of proliferation, and anchorage-dependent and anchorage-independent clonal growth of MPM cells.…”
Section: Functional Genomics Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…Functional consequences of deregulations in ZEB1, ERβ, SP1, and WT1 zinc-finger transcription factors are well studied in breast cancer, lung cancer, pancreatic cancer, and prostate cancer [ 169 , 170 , 171 , 172 ]. Recently, the upregulation of these genes has been shown in MPM, when compared to matched normal counterparts [ 173 , 174 , 175 , 176 ]. Horio et al showed that siRNA-mediated knockdown of ZEB1 (zinc finger e-box binding homeobox 1) led to the suppression of proliferation, and anchorage-dependent and anchorage-independent clonal growth of MPM cells.…”
Section: Functional Genomics Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…The transcription regulation of MIT depends on a non-covalent interaction with GC-rich DNA regions, especially the site of union of Sp1 transcription factor. 11 MIT was shown to have antiangiogenic effect in …”
Section: Discussionmentioning
confidence: 99%
“…8,9 It was also shown that MIT inhibited DNA methyltransferase (DNMT), histone deacetylase (HDAC), and antiapoptotic protein XIAP. [10][11][12] Preclinical studies demonstrated that MIT can inhibit the generation and progression of several cancers, including carcinomas of the lung, breast, pancreas, stomach, and prostate, as well as sarcoma and glioblastoma. 8,[13][14][15][16] Meanwhile, its prominent in vitro and in vivo activities linked to specific transcription regulation have triggered the clinical trials of MIT in lung cancer, esophagus cancer, and Ewing sarcoma, sponsored by the National Cancer Institute (NCT01610570, NCT01624090, and NCT02859415, www.ClinicalTrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR, immunoblot and IHC experiments demonstrated markedly higher SP1 expression levels in MPM lines and primary MPMs relative to cultured normal mesothelia or normal pleura. Over-expression or knock-down of SP1 significantly increased or decreased EZH2 expression, respectively; furthermore, knock-down of SP1 diminished proliferation of MPM cells (102).…”
Section: Polycomb Mediated Gene Silencingmentioning
confidence: 92%